Epoxy resin solid electrolyte and preparation method and application thereof

By introducing ionic conductive group compounds and flexible chain segments into epoxy resins, a three-dimensional grid structure is formed, and a microporous structure is formed using pore-forming agents, the problems of low conductivity and insufficient mechanical strength of solid electrolytes are solved, and high Improved electrical conductivity and mechanical strength.

CN119170867AInactive Publication Date: 2024-12-20SHENZHEN NO 1 FINE CHEM CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411575627.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing solid electrolytes have low conductivity and insufficient mechanical strength, making it difficult to meet the safety and energy density requirements of modern electrochemical devices.

Method used

Epoxy resin is used as the main matrix, combining ionic conductive group compounds, flexible segment compounds and pore-forming agents, and a three-dimensional grid structure and microporous structure are formed through cross-linking reactions to improve ionic conductivity and mechanical strength.

Benefits of technology

It significantly improves the conductivity and mechanical strength of the solid electrolyte, ensures good ion migration channels and chemical stability, and overcomes the limitations of traditional solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121720970000051
    Figure BDA0005121720970000051
  • Figure BDA0005121720970000052
    Figure BDA0005121720970000052
  • Figure BDA0005121720970000053
    Figure BDA0005121720970000053
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical materials, and discloses an epoxy resin solid electrolyte as well as a preparation method and application thereof. The preparation raw materials are as follows: 100 parts of epoxy resin, 5-15 parts of an ionic conductive group compound, 5-15 parts of a high ionic conductive lithium salt, 2-20 parts of an ionic liquid, 10-30 parts of a flexible chain segment compound, 1-20 parts of a pore forming agent and 20-50 parts of a curing agent. The ionic conductive group compound comprises a sulfonic compound, a quaternary ammonium salt or a carboxyl compound; the flexible chain segment compound comprises one or more of polyester, polyurethane, polyacrylate, polyacrylic acid, polyamide and polyether-ether-ketone. According to the invention, the epoxy resin is used as a main matrix, the ionic liquid provides an ionic migration path, meanwhile, an ionic conductive group is grafted into an epoxy resin molecule, a flexible chain segment is introduced to reduce the crosslinking density, and the cured electrolyte matrix can form an effective ion channel, so that the conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical materials, and in particular to an epoxy resin solid electrolyte and a preparation method and application thereof. Background Art

[0002] Solid-state electrolytes have broad application prospects in modern electrochemical devices, especially in improving safety, energy density and electrochemical stability. Traditional liquid electrolytes have potential safety hazards due to their flammability, volatility and corrosiveness, especially when used in lithium-ion batteries, they are prone to thermal runaway. Solid-state electrolytes can effectively solve these problems, but most existing solid-state electrolytes are based on inorganic materials and have defects such as low conductivity and insufficient mechanical strength. Summary of the invention

[0003] The purpose of the present invention is to provide an epoxy resin solid electrolyte and a preparation method and application thereof, so as to solve the problems of low conductivity and insufficient mechanical strength of existing solid electrolytes.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides an epoxy resin solid electrolyte, comprising the following raw materials in parts by weight:

[0006] 100 parts of epoxy resin, 5-15 parts of ion conductive group compound, 5-15 parts of high ion conductive lithium salt, 2-20 parts of ionic liquid, 10-30 parts of flexible segment compound, 1-20 parts of pore former, 20-50 parts of curing agent;

[0007] The ion-conductive group compound includes a sulfonic acid compound, a quaternary ammonium salt compound or a carboxyl compound;

[0008] The high ion conductivity lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium iodide and lithium bis(trifluoromethanesulfonyl)imide;

[0009] The flexible segment compound includes one or more of polyester, polyurethane, polyacrylate, polyacrylic acid, polyamide and polyetheretherketone.

[0010] Preferably, 1 to 10 parts of carbon material are also included.

[0011] Preferably, the epoxy resin includes one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, linear aliphatic epoxy resin, polyurethane modified epoxy resin, heterocyclic or special structure epoxy resin;

[0012] The glycidyl ether epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic alcohol epoxy resin, phenol formaldehyde epoxy resin, o-cresol epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol AD ​​epoxy resin, hydroxymethyl bisphenol A epoxy resin, brominated epoxy resin, and phosphorus-containing epoxy resin;

[0013] The glycidyl ester epoxy resin includes one or more of diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, diglycidyl isophthalate, diglycidyl terephthalate, diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, diglycidyl cyclohexane-1,2-dicarboxylate and diglycidyl 4,5-epoxycyclohexane-1,2-dicarboxylate;

[0014] The glycidylamine epoxy resin includes one or more of a bifunctional amino epoxy resin, a trifunctional amino epoxy resin, a quadrifunctional amino epoxy resin, and a multifunctional amino epoxy resin;

[0015] The alicyclic epoxy resin includes one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, bis((3,4-epoxycyclohexyl)methyl) adipate, poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 1,2-epoxy-4-vinylcyclohexane, vinylcyclohexene dioxide, epoxidized tetrahydrofuran, and epoxidized cyclopentene;

[0016] The linear aliphatic epoxy resin includes one or more of aliphatic alcohol epoxy resin, polyester epoxy resin, and polyether epoxy resin;

[0017] The heterocyclic or special structure epoxy resin includes one or more of polyethersulfoneketone epoxy resin, liquid crystal epoxy resin, polysiloxane copolymer modified epoxy resin, dicyclopentadiene epoxy resin, crystalline epoxy resin, furan epoxy resin, thiophene epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, and hydantoin epoxy resin;

[0018] The curing agent includes one or more of an amine curing agent, an acid anhydride curing agent, an imidazole curing agent, and a phenolic curing agent.

[0019] Preferably, the ionic liquid is one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium chloride, and trioctylmethylammonium chloride tetrafluoroborate.

[0020] Preferably, the sulfonic acid compound includes one or more of sodium sulfonate, lithium sulfonate, sulfonated polystyrene, and sulfonated polyetheretherketone;

[0021] The quaternary ammonium salt compound includes one or more of tetramethylammonium fluoride, tetraethylammonium salt, and tetramethylammonium chloride;

[0022] The carboxyl compound includes one or more of sodium acetate, sodium acrylate and polylactic acid.

[0023] Preferably, the pore-forming agent is nanoparticles and / or a foaming agent;

[0024] The nanoparticles include one or more of aluminum oxide, silicon dioxide, graphene, carbon nanotubes, and titanium dioxide;

[0025] The foaming agent includes one or more of polystyrene, polyurethane, butane, freon, sodium bicarbonate and amino acid.

[0026] The present invention also provides a method for preparing the epoxy resin solid electrolyte, comprising the following steps:

[0027] The epoxy resin solid electrolyte is obtained by mixing the raw materials, pouring and curing.

[0028] Preferably, the curing temperature is 60-120° C. and the curing time is 2-6 hours.

[0029] The present invention also provides application of the epoxy resin solid electrolyte in batteries, capacitors, sensors or flexible electronic devices.

[0030] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0031] The epoxy resin solid electrolyte provided by the present invention uses epoxy resin as the main matrix and ionic liquid as an auxiliary to provide an ion migration path. At the same time, the ion conductive groups in the ion conductive group compound are grafted into the epoxy resin molecules, and a flexible segment compound is introduced to reduce the cross-linking density, ensuring that the cured electrolyte matrix can form an effective ion channel, thereby improving the conductive performance.

[0032] The present invention adopts an ion conduction mechanism to ensure that the solid electrolyte still has a good ion migration channel after solidification and maintains high mechanical strength and chemical stability, so as to overcome the limitations of traditional solid electrolytes.

[0033] The epoxy resin solid electrolyte in the present invention is a three-dimensional grid structure, wherein the epoxy resin molecular chains form a three-dimensional network structure through cross-linking, and the ion conductive groups in the ion conductive group compound are evenly distributed in the resin matrix to form ion migration channels. This structure helps to improve the ion conductivity of the material.

[0034] In the epoxy resin solid electrolyte of the present invention, the mobility of the epoxy resin chain segments is relatively high at the initial stage of the crosslinking reaction. As the crosslinking reaction proceeds, the ion conductive groups gradually form a network structure, and finally form a stable ion migration channel while crosslinking, thereby improving the conductivity of the electrolyte. That is, in the initial stage, the epoxy resin chain segments move freely and the ion groups are dispersed; in the intermediate state, the epoxy resin chain segments begin to crosslink, and the ion groups gather to form preliminary channels; in the final state, a stable crosslinking network and ion migration channels are formed, indicating that the chain segments are fixed.

[0035] The epoxy resin solid electrolyte of the present invention introduces a pore-forming agent to form a microporous structure with uniform pore size distribution and adjustable porosity. The formation of the microporous structure not only increases the ion migration path, but also provides a larger contact area, thereby further improving the ionic conductivity and overall performance of the electrolyte. DETAILED DESCRIPTION

[0036] The present invention provides an epoxy resin solid electrolyte, comprising the following raw materials in parts by weight:

[0037] 100 parts of epoxy resin, 5-15 parts of ion conductive group compound, 5-15 parts of high ion conductive lithium salt, 2-20 parts of ionic liquid, 10-30 parts of flexible segment compound, 1-20 parts of pore former and 20-50 parts of curing agent.

[0038] In the present invention, the mass fraction of the epoxy resin is preferably 100 parts.

[0039] In the present invention, the mass fraction of the ion-conductive group compound is preferably 5 to 15 parts, more preferably 6 to 13 parts, and even more preferably 8 to 10 parts.

[0040] In the present invention, the mass fraction of the highly ion-conductive lithium salt is preferably 5 to 15 parts, more preferably 6 to 13 parts, and even more preferably 8 to 10 parts.

[0041] In the present invention, the mass fraction of the ionic liquid is preferably 2 to 20 parts, more preferably 5 to 17 parts, and even more preferably 8 to 13 parts.

[0042] In the present invention, the weight fraction of the soft segment compound is preferably 10 to 30 parts, more preferably 11 to 26 parts, and even more preferably 13 to 21 parts.

[0043] In the present invention, the mass fraction of the pore former is preferably 1 to 20 parts, more preferably 3 to 17 parts, and even more preferably 5 to 15 parts.

[0044] In the present invention, the mass fraction of the curing agent is preferably 20 to 50 parts, more preferably 25 to 40 parts, and even more preferably 28 to 33 parts.

[0045] In the present invention, the epoxy resin solid electrolyte further comprises 1 to 10 parts of carbon material, more preferably 2 to 8 parts, and even more preferably 3 to 6 parts.

[0046] In the present invention, the epoxy resin preferably includes one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, linear aliphatic epoxy resin, polyurethane modified epoxy resin, heterocyclic or special structure epoxy resin.

[0047] In the present invention, the glycidyl ether epoxy resin preferably includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic alcohol epoxy resin, phenol formaldehyde epoxy resin, o-cresol epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol AD ​​epoxy resin, hydroxymethyl bisphenol A epoxy resin, brominated epoxy resin, and phosphorus-containing epoxy resin.

[0048] In the present invention, the glycidyl ester type epoxy resin preferably includes one or more of diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, diglycidyl isophthalate, diglycidyl terephthalate, diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, diglycidyl cyclohexane-1,2-dicarboxylate and diglycidyl 4,5-epoxycyclohexane-1,2-dicarboxylate.

[0049] In the present invention, the glycidylamine epoxy resin preferably includes one or more of a bifunctional amino epoxy resin, a trifunctional amino epoxy resin, a tetrafunctional amino epoxy resin, and a multifunctional amino epoxy resin.

[0050] In the present invention, the structure of the bifunctional amino epoxy resin is as follows:

[0051]

[0052] In the present invention, the structure of the trifunctional amino epoxy resin is as follows:

[0053]

[0054] In the present invention, the structure of the 4-functional amino epoxy resin is as follows:

[0055]

[0056] In the present invention, the multifunctional amino epoxy resin includes: diaminodiphenylmethane type epoxy resin or diaminodiphenyl ether type epoxy resin, which are prepared by reacting diaminodiphenylmethane with epichlorohydrin;

[0057] Diaminodiphenyl sulfone type epoxy resins prepared by reacting diaminodiphenyl sulfone with epichlorohydrin;

[0058] Aminophenol-type epoxy resins prepared by reacting aminophenol with epichlorohydrin;

[0059] Meta-xylylenediamine (MXDA) type epoxy resins prepared by reacting meta-xylylenediamine with epichlorohydrin;

[0060] 1,3-bisaminomethylcyclohexane type epoxy resin, which is prepared by reacting 1,3-bisaminomethylcyclohexane with epichlorohydrin;

[0061] Isocyanurate type epoxy resins prepared by reacting isocyanurate with epichlorohydrin, such as tris(2,3-epoxypropyl)isocyanurate).

[0062] In the present invention, the alicyclic epoxy resin preferably includes one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 1,2-epoxy-4-vinylcyclohexane, vinylcyclohexene dioxide, epoxidized tetrahydrofuran, and epoxidized cyclopentene.

[0063] In the present invention, the linear aliphatic epoxy resin preferably includes one or more of aliphatic alcohol epoxy resin, polyester epoxy resin, and polyether epoxy resin.

[0064] In the present invention, the heterocyclic or special structure epoxy resin preferably includes one or more of polyethersulfoneketone epoxy resin, liquid crystal epoxy resin, polysiloxane copolymer modified epoxy resin, dicyclopentadiene epoxy resin, crystalline epoxy resin, furan epoxy resin, thiophene epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, and hydantoin epoxy resin.

[0065] In the present invention, the epoxy resin is purchased from Jiangsu Taitel New Material Technology Co., Ltd.

[0066] In the present invention, the ion-conductive group compound includes a sulfonic acid compound, a quaternary ammonium salt compound or a carboxyl compound.

[0067] In the present invention, the sulfonic acid compound preferably includes one or more of sodium sulfonate, lithium sulfonate, sulfonated polystyrene, and sulfonated polyetheretherketone; the structure of sulfonated polystyrene can effectively enhance the conductivity, mechanical strength and film-forming properties of the epoxy solid electrolyte; sulfonated polyetheretherketone has excellent proton conductivity and thermal stability.

[0068] In the present invention, the quaternary ammonium salt compound preferably includes one or more of tetramethylammonium fluoride, tetraethylammonium salt, and tetramethylammonium chloride; tetramethylammonium fluoride, as a highly efficient quaternary ammonium salt, helps to improve ionic conductivity.

[0069] In the present invention, the carboxyl compound preferably includes one or more of sodium acetate, sodium acrylate, and polylactic acid.

[0070] In the present invention, the high ion conductive lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium iodide and lithium bis(trifluoromethanesulfonyl)imide.

[0071] In the present invention, the ionic liquid is preferably one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium chloride, and trioctylmethylammonium chloride tetrafluoroborate.

[0072] In the present invention, the flexible segment compound preferably includes one or more of polyester, polyurethane, polyacrylate, polyacrylic acid, polyamide, and polyetheretherketone. The role of the flexible segment compound is to promote the formation of ion channels; polyacrylic acid can provide good flexibility and hydration capacity in the electrolyte; polyetheretherketone: as a choice of high temperature resistance and chemical stability, it provides excellent flexibility and mechanical properties.

[0073] In the present invention, the polyester preferably includes one or both of polylactic acid and polyethylene terephthalate. Polylactic acid: provides good flexibility and has biocompatibility, which is conducive to environmentally friendly applications; polyethylene terephthalate: is suitable for improving the flexibility and toughness of the film.

[0074] In the present invention, the polyurethane is preferably thermoplastic polyurethane. Thermoplastic polyurethane: has excellent toughness and wear resistance, and can improve the mechanical properties of the film.

[0075] In the present invention, the polyamide is preferably ternary copolymer alcohol-soluble nylon. By using ternary copolymer alcohol-soluble nylon as a toughening agent and an epoxy resin matrix to form a uniform dispersion system, the flexibility of the electrolyte is ensured, the ionic conductivity and mechanical strength of the electrolyte are improved, and the overall performance of the solid-state battery is further improved.

[0076] In the present invention, the ternary copolymer alcohol-soluble nylon is purchased from Shanghai Zhenwei Composite Materials Co., Ltd., and the models are ES-1, ES-2, ES-3, and ES-4.

[0077] In the present invention, the pore former is preferably nanoparticles and / or foaming agent.

[0078] In the present invention, the nanoparticles preferably include one or more of aluminum oxide, silicon dioxide, graphene, carbon nanotubes, and titanium dioxide.

[0079] In the present invention, the foaming agent preferably includes one or more of polystyrene, polyurethane, butane, freon, sodium bicarbonate, and amino acid.

[0080] In the present invention, when the foaming agent and the nanoparticles are selected at the same time, the masses of the two are the same.

[0081] In the present invention, the curing agent preferably includes one or more of an amine curing agent, an acid anhydride curing agent, an imidazole curing agent, and a phenolic curing agent.

[0082] In the present invention, the carbon material preferably includes one or more of carbon fiber, carbon black, graphene, and carbon nanotubes.

[0083] The present invention also provides a method for preparing an epoxy resin solid electrolyte, comprising the following steps:

[0084] The epoxy resin solid electrolyte is obtained by mixing the raw materials, pouring and curing.

[0085] In the present invention, the pore former forms a microporous structure to increase the effectiveness of the ion migration channel.

[0086] In the present invention, a template is made of a suitable template material according to the electrolyte shape required in actual conditions; the raw materials are evenly mixed and poured into the template for curing, and the template is physically demoulded after curing to obtain an epoxy resin solid electrolyte.

[0087] In the present invention, the curing temperature is preferably 60 to 120° C., more preferably 65 to 110° C., and more preferably 70 to 95° C.; the curing time is preferably 2 to 6 hours, more preferably 2.5 to 5 hours, and more preferably 3 to 4 hours.

[0088] The present invention also provides an application of an epoxy resin solid electrolyte in a battery, a capacitor, a sensor or a flexible electronic device.

[0089] In the present invention, the battery is preferably a lithium battery, a sodium battery or a fuel cell.

[0090] In the present invention, the capacitor is preferably a supercapacitor.

[0091] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0092] Example 1

[0093] A method for preparing an epoxy resin solid electrolyte comprises the following steps:

[0094] 100 parts of epoxy resin, 10 parts of high ion conductive lithium salt, 10 parts of ion conductive group compound, 10 parts of ionic liquid, 20 parts of flexible segment compound, 10 parts of pore former and 33 parts of curing agent were mixed evenly and poured into a polymer template. The mixture was cured at 100°C for 4 hours. After the curing was completed, the template was removed by physical methods to obtain an epoxy resin solid electrolyte.

[0095] The epoxy resin is a mixture of bisphenol F epoxy resin and phenol formaldehyde epoxy resin (mass ratio is 1:1);

[0096] The curing agent is a mixture of polyetheramine D230 and 4,4'-diaminodicyclohexylmethane (HMDA) (mass ratio is 4:6);

[0097] The ion-conducting group compound is sulfonated polystyrene;

[0098] The high ionic conductivity lithium salt is lithium hexafluorophosphate;

[0099] The ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate;

[0100] The flexible segment compound is thermoplastic polyurethane;

[0101] The nanoparticles are nano-alumina.

[0102] The foaming agent is a mixture of polystyrene foam and sodium bicarbonate (mass ratio is 7:3).

[0103] Example 2

[0104] 100 parts of epoxy resin, 15 parts of high ion conductive lithium salt, 10 parts of ion conductive group compound, 10 parts of ionic liquid, 20 parts of flexible segment compound, 15 parts of pore former and 33 parts of curing agent were mixed evenly and poured into a polymer template. The mixture was cured at 80°C for 4 hours. After the curing was completed, the template was removed by physical methods to obtain an epoxy resin solid electrolyte.

[0105] The epoxy resin is a mixture of bisphenol A epoxy resin and phenol formaldehyde epoxy resin (mass ratio is 5:5);

[0106] The curing agent is a mixture of polyetheramine T403 and 4,4'-diaminodiphenylmethane (DDM) (mass ratio is 3:7);

[0107] The ion-conducting group compound is sulfonated polyetheretherketone;

[0108] The high ionic conductivity lithium salt is lithium tetrafluoroborate

[0109] The ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate;

[0110] The flexible segment compound is thermoplastic polyurethane;

[0111] The nanoparticles are carbon nanotubes;

[0112] The foaming agent is a mixture of polystyrene foam and sodium bicarbonate (mass ratio is 6:4).

[0113] Example 3

[0114] A method for preparing an epoxy resin solid electrolyte comprises the following steps:

[0115] 100 parts of epoxy resin, 10 parts of high ion conductive lithium salt, 10 parts of ion conductive group compound, 15 parts of ionic liquid, 20 parts of flexible segment compound, 5 parts of pore former, 28 parts of curing agent and 3 parts of carbon material were mixed evenly and poured into a polymer template. The mixture was cured at 115°C for 5 hours. After the curing was completed, the template was removed by physical methods to obtain an epoxy resin solid electrolyte.

[0116] The epoxy resin is a mixture of bisphenol F epoxy resin, polyurethane modified epoxy resin and phenol formaldehyde epoxy resin (mass ratio is 3:2:5);

[0117] The curing agent is a mixture of polyetheramine D230, isophorone diamine IPDA and 4,4'-diaminodiphenylmethane (DDM) (mass ratio is 3:3:4);

[0118] The carbon material is a mixture of carbon nanotubes and graphene (mass ratio is 5:5);

[0119] The ion-conducting group compound is sulfonated polyetheretherketone;

[0120] The lithium salt with high ionic conductivity is lithium perchlorate

[0121] The ionic liquid is trioctylmethylammonium chloride tetrafluoroborate;

[0122] The flexible segment compound is ternary copolymer alcohol-soluble nylon;

[0123] The nanoparticles are graphene;

[0124] The foaming agent is a mixture of polystyrene foam and sodium bicarbonate (mass ratio is 5:5).

[0125] Performance Testing

[0126] 1. Ionic conductivity test

[0127] Test method: Use the electrochemical impedance spectroscopy (EIS) test method;

[0128] Equipment: Electrochemical workstation;

[0129] Sample preparation: The epoxy resin solid electrolyte was made into a disc sample with a diameter of 10 mm and a thickness of 1 mm;

[0130] Test steps:

[0131] The sample is placed in the test cell, sandwiched between two electrodes.

[0132] Apply an AC signal in the frequency range of 1 Hz to 1 MHz and record the impedance spectrum;

[0133] The conductivity of the sample was obtained by Nyquist plot analysis;

[0134] Calculation formula:

[0135] σ=d / (R·A);

[0136] Among them, σ is the conductivity, d is the sample thickness, R is the DC resistance of the battery, and A is the electrode area.

[0137] 2. Mechanical properties test

[0138] Test method: Use tensile test;

[0139] Equipment: Material testing machine.

[0140] Sample preparation: tensile specimens were prepared according to ASTM D638 standard, and the standard size was dog tooth shape;

[0141] Test steps:

[0142] The sample was placed in a material testing machine and stretched at a standard rate of 5 mm / min. The stress-strain curve was recorded to obtain the tensile strength, elongation at break and Young's modulus of the material.

[0143] The performance test results of the epoxy resin solid electrolytes in Examples 1 to 3 are shown in Table 1.

[0144] Table 1 Performance test results of epoxy resin solid electrolyte in Examples 1 to 3

[0145]

[0146] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An epoxy resin solid electrolyte, characterized in that: Contains the following raw materials by weight: 100 parts of epoxy resin, 5-15 parts of ion conductive group compound, 5-15 parts of high ion conductive lithium salt, 2-20 parts of ionic liquid, 10-30 parts of flexible segment compound, 1-20 parts of pore former, 20-50 parts of curing agent; The ion-conductive group compound includes a sulfonic acid compound, a quaternary ammonium salt compound or a carboxyl compound; The high ion conductivity lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium iodide and lithium bis(trifluoromethanesulfonyl)imide; The flexible segment compound includes one or more of polyester, polyurethane, polyacrylate, polyacrylic acid, polyamide and polyetheretherketone.

2. The epoxy resin solid electrolyte according to claim 1, characterized in that: It also includes 1 to 10 parts of carbon material.

3. The epoxy resin solid electrolyte according to claim 2, characterized in that: The epoxy resin includes one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, linear aliphatic epoxy resin, polyurethane modified epoxy resin, heterocyclic or special structure epoxy resin; The glycidyl ether epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic alcohol epoxy resin, phenol formaldehyde epoxy resin, o-cresol epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol AD ​​epoxy resin, hydroxymethyl bisphenol A epoxy resin, brominated epoxy resin, and phosphorus-containing epoxy resin; The glycidyl ester epoxy resin includes one or more of diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, diglycidyl isophthalate, diglycidyl terephthalate, diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, diglycidyl cyclohexane-1,2-dicarboxylate and diglycidyl 4,5-epoxycyclohexane-1,2-dicarboxylate; The glycidylamine epoxy resin includes one or more of a bifunctional amino epoxy resin, a trifunctional amino epoxy resin, a quadrifunctional amino epoxy resin, and a multifunctional amino epoxy resin; The alicyclic epoxy resin includes one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, bis((3,4-epoxycyclohexyl)methyl) adipate, poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 1,2-epoxy-4-vinylcyclohexane, vinylcyclohexene dioxide, epoxidized tetrahydrofuran, and epoxidized cyclopentene; The linear aliphatic epoxy resin includes one or more of aliphatic alcohol epoxy resin, polyester epoxy resin, and polyether epoxy resin; The heterocyclic or special structure epoxy resin includes one or more of polyethersulfoneketone epoxy resin, liquid crystal epoxy resin, polysiloxane copolymer modified epoxy resin, dicyclopentadiene epoxy resin, crystalline epoxy resin, furan epoxy resin, thiophene epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, and hydantoin epoxy resin; The curing agent includes one or more of an amine curing agent, an acid anhydride curing agent, an imidazole curing agent, and a phenolic curing agent.

4. The epoxy resin solid electrolyte according to claim 3, characterized in that: The ionic liquid is one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium chloride, and trioctylmethylammonium chloride tetrafluoroborate.

5. The epoxy resin solid electrolyte according to claim 4, characterized in that: The sulfonic acid compound includes one or more of sodium sulfonate, lithium sulfonate, sulfonated polystyrene, and sulfonated polyetheretherketone; The quaternary ammonium salt compound includes one or more of tetramethylammonium fluoride, tetraethylammonium salt, and tetramethylammonium chloride; The carboxyl compound includes one or more of sodium acetate, sodium acrylate and polylactic acid.

6. The epoxy resin solid electrolyte according to claim 5, characterized in that: The pore-forming agent is nanoparticles and / or foaming agent; The nanoparticles include one or more of aluminum oxide, silicon dioxide, graphene, carbon nanotubes, and titanium dioxide; The foaming agent includes one or more of polystyrene, polyurethane, butane, freon, sodium bicarbonate and amino acid.

7. The method for preparing the epoxy resin solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: The epoxy resin solid electrolyte is obtained by mixing the raw materials, pouring and curing.

8. The method for preparing the epoxy resin solid electrolyte according to claim 7, characterized in that: The curing temperature is 60-120° C. and the curing time is 2-6 hours.

9. Use of the epoxy resin solid electrolyte according to any one of claims 1 to 6 in batteries, capacitors, sensors or flexible electronic devices.

Citation Information

Cited By

  • Resin-based electrolyte, preparation method thereof and application of resin-based electrolyte in structural energy storage composite material

    CN119965338A

  • Solid-state electrolyte, solid-state battery and preparation method

    CN120637570A

  • Silicon-containing cycloaliphatic epoxy resin-based gel polymer electrolyte, and preparation method and application thereof

    CN122716415A

  • Silicon-containing cycloaliphatic epoxy resin-based gel polymer electrolyte, and preparation method and application thereof

    CN122716415B